The Life Mission Theory IV. Theory on Child Development - Soren Ventegodt; Joav Merrick (The Scientific World Journal)
We can identify five important needs that children have: the need for acknowledgment, acceptance, awareness or attention, respect, and care. If these needs are not met, children will modify themselves by denying central parts of their nature in order to adjust to their parents and the situation at large. When a child denies his or her talents, powers, and gender or aspects thereof, he or she loses quality of life, the ability to function, and physical or mental health. The loss of ability takes the form of diminished social ability, psychosexual potency, joy, energy, and fantasy while playing, as well as diminished ability to concentrate, focus, and learn. Many modifications result in a child with severely damaged self-confidence, self-worth, and poor performance. A child more or less deprived of self-worth cannot enjoy, give, or receive. A child deprived of emotions turns cold, rational, asocial, socially stiff, uncomfortable, and in the extreme case... intentionally “evil”. When a child denies his or her own sex, it becomes invisible, uninteresting, and vague or becomes like the opposite sex in behavior and appearance. The general holistic solution to the vast diversity of symptoms in children with low quality of life is to improve the situation for the child and give the child the holding and support he or she needs. It is very important to realize that a negative belief often has survival value to the child as it helps the child to avoid taking responsibility for problems, which really belong to the parents or other adults. Children have a fine capability for spontaneous healing, and seem to enter this process more easily than adults, given sufficient holding. The symptoms of children with poor thriving ability are often difficult to understand, as they are caused by a complex combination of self-modification in five existential dimensions. This often leads to complex medical diagnosis, giving the idea that the child is sick and without therapeutic reach, while sufficient holding could solve the problem. If holding and support of the child is not enough, the situation must be carefully analyzed to find other possible causes of poor quality of life, health, and functional ability. Education of the parent in holding is often mandatory. Most children with bad thriving ability can thus be helped by simple means.